Validity of the Arbitration Clause in the International Employment Contract: the Viewpoint of the GCC Countries - Al-Sharaf, Sharaf Khaled; Al-Tourah, Anas Faisal (Comparative Law Review, 2023)
In this paper we will evaluate the significance of the arbitration clause in international employment contracts. Our aim is to understand how this particular alternative dispute resolution (ADR) mechanism is utilized in the Gulf Cooperation Council (GCC) countries. Even though the law in several countries aims to protect employees by prohibiting arbitration agreements (due to considerations of employee protection), we argue that it should be optional for the employee to enter into labour agreements with arbitration clauses. This is especially important when the arbitration agreement achieves the employees’ interests, and is agreed upon with informed and clear consent. We will engage with arguments which advocate the prohibition of arbitration agreements within Individual Employment Contracts (IECs); whilst taking the position that the flexibility, speed, confidentiality and predictability of arbitration provides specific advantages to international employees compared to litigation before court. Furthermore, in the context of a desire on the side of GCC countries to attract high-skilled labour (and when there are many misconceptions regarding the adjudicative functions of labour law courts in the GCC), arbitration clauses can play a significant role in mediating between different legal cultures.